TPACK in Practice: EFL Pre-service Teachers on Integrating Technology during Online Teaching in Thailand - Adelina Ayu Lestari; Slamet Asari (JELLT (Journal of English Language and Language Teaching), 2022)
Before the COVID-19 Pandemic, teaching activities were usually done directly at school, now it had to be done virtually. It also impacts teachers and students, who must use technology during learning activities to get maximum results. Likewise, pre-service teachers who carry out teaching activities in Thailand must choose the appropriate technology for them as a learning medium. Therefore, this study explores how EFL pre-service teachers integrate technology for online learning activities and their views on students when integrating technology during teaching-learning activities. The qualitative case study was used in this research, using observation, interviews, and document analysis as the instrument to collect data. Two students in the 5th semester from the English department participated in an internship held from June to March 2021. The results are participants have recognized and used various kinds of technology that are usually used in learning activities. The use of videos, and PowerPoint are the most frequently used by participants because of the ease of use, which impact students’ understanding positively on the material being taught and become more active in class. Moreover, the various technologies used in teaching and learning activities can make it easier for teachers to find and deliver learning materials.